Question Number 1 :
For this function y(x)=( x + 2 ) * ( x - 3 ) , answer the following questions :
A. Looks for some points in the curve and plot the curve !
Answer Number 1 :
First, we must turn this equation ( x + 2 ) * ( x - 3 ) = 0 into a*x^2+b*x+c=0 form.
( x + 2 ) * ( x - 3 ) = 0 , expand the left hand side.
<=> x * ( x - 3 ) + 2 * ( x - 3 ) = 0
<=> x^2 - x - 6 = 0 , move 0 from the right hand side to the left hand side.
<=> x^2 - x - 6 - 0 = 0
<=> x^2 - x - 6 = 0
The equation x^2 - x - 6 = 0 is already in a*x^2+b*x+c=0 form.
As the value is already arranged in a*x^2+b*x+c=0 form, we get the value of a = 1, b = -1, c = -6.
1A. Looks for some points in the curve and plot the curve !
y(x) = x^2 - x - 6
y(-6) = (-6)^2 - (-6) - 6 = 36 -> ( (-6) , y ) = ( -6 , 36 )
y(-5) = (-5)^2 - (-5) - 6 = 24 -> ( (-5) , y ) = ( -5 , 24 )
y(-4) = (-4)^2 - (-4) - 6 = 14 -> ( (-4) , y ) = ( -4 , 14 ) <- this is the answer x=-4
y(-3) = (-3)^2 - (-3) - 6 = 6 -> ( (-3) , y ) = ( -3 , 6 )
y(-2) = (-2)^2 - (-2) - 6 = 0 -> ( (-2) , y ) = ( -2 , 0 )
y(-1) = (-1)^2 - (-1) - 6 = -4 -> ( (-1) , y ) = ( -1 , -4 )
y(0) = (0)^2 - (0) - 6 = -6 -> ( (0) , y ) = ( 0 , -6 )
y(1) = (1)^2 - (1) - 6 = -6 -> ( (1) , y ) = ( 1 , -6 )
y(2) = (2)^2 - (2) - 6 = -4 -> ( (2) , y ) = ( 2 , -4 )
y(3) = (3)^2 - (3) - 6 = 0 -> ( (3) , y ) = ( 3 , 0 )
y(4) = (4)^2 - (4) - 6 = 6 -> ( (4) , y ) = ( 4 , 6 )
y(5) = (5)^2 - (5) - 6 = 14 -> ( (5) , y ) = ( 5 , 14 ) <- this is the answer x=5
y(6) = (6)^2 - (6) - 6 = 24 -> ( (6) , y ) = ( 6 , 24 )
The answers are : x=-4 and x=5